Interaction of Kinetin and Calcium in Relation to Their Effect on Stimulation of Ethylene Production - Lau, Oi-Lim (1975)
Application of kinetin and Ca(2+) caused a striking synergistic increase in ethylene production by mung bean (Phaseolus aureus Roxb) hypocotyl segments. The effect of kinetin on Ca(2+) uptake and of Ca(2+) on the uptake and metabolism of kinetin in relation to their effect on ethylene production was studied. Tracer experiments showed that kinetin greatly increased the uptake of (45)Ca(2+) after 6 hours of incubation. Reciprocally, Ca(2+) stimulated the uptake of kinetin-8-(14)C and remarkably enhanced the metabolism of kinetin-8-(14)C into several polar metabolites. Consequently, the quantity of free kinetin-8-(14)C remaining in Ca(2+)-treated segments was much less than in control segments. A possible mechanism accounting for the synergism between kinetin and calcium on ethylene production is discussed.